International Tax Competitiveness Index 2018 - (:unkn) unknown (My University, 2020)
Η παρούσα εργασία έχει ως κύριο θέμα της την μελέτη του διεθνή δείκτη ανταγωνισμού για το έτος 2018 σε διάφορες χώρες του κόσμου. Επίσης αναλύει διάφορα είδη φόρων και εξηγεί τη χρησιμότητα τους.

The main topic of this paper is the study of the international competition index for the year 2018 in various countries around the world. It also analyzes the different types of taxes and explains their usefulness.
Keywords: διεθνής δείκτης ανταγωνισμού, οικονομία, εισόδημα, φορολογία; international competitiveness index, economy, income, taxation